The Gender Trap : Parents and the Pitfalls of Raising Boys and Girls - Kane, Emily W. (Book collections on Project MUSE., 2012)
"Emily Kane shows clearly that most parents understand children's personality to be some combination of nature and nurture, and many wish they could help nurture their children to escape gender traps. Yet these parents are themselves trapped by the gender structure itself, especially the accountability they feel to other people's expectations, and the fear that if their boys are free to explore activities usually associated with girls they will be punished by the world around them. The author shows clearly that to help parents navigate childrearing, we have to change the world around them. A good read, perfect for the undergraduate classroom, and clear enough even to give to those new parents in your family or the neighborhood."--Cover.